Accessing ankle kinematics in sagittal and frontal planes of motion by accelerometers during gait: an inexpensive alternative to optical motion analysis systems - Trede Filho, Renato Guilherme; Sono, Tálita Saemi Payossim; Pereira, Isabela Lurdes Miranda; Barbosa, Ana Clara Dvilla Gonçalves; Magalhães, Fabrício Anicio; Brant, Alicia Corrêa; Costa, Henrique Silveira; Gomes, Rosalina Tossige; Pertence, Antônio Eustáquio de Melo (Revista Vozes dos Vales: Publicações Acadêmicas, 2024)
kinematics in the sagittal and frontal planes of motion during gait. Material and methods: Two triaxial accelerometers were attached to the leg and foot of ten healthy volunteers. Gait kinematic data was compared with data obtained from an optical motion analysis system. Results: The pattern of the curves obtained using the accelerometer-based system is similar to that obtained by the optical motion analysis system, especially in the range of 0 to 60% of the gait cycle. Isolating the stance phase of gait, the coefficient of multiple correlation for the kinematic data of two systems was CMC = 0.99 for the sagittal plane and CMC = 0.97 for the frontal plane motion. The maximal RMS error in the stance phase of gait was 1.6 degrees in the sagittal plane of motion. Conclusion: The accelerometer-based system has low cost and accurate data of ankle kinematic in the stance phase of gait when compared to optical motion analysis systems